Pengawal Lampu Trafik Dengan Pengesan Menggunakan FPGA - Shafiee, Mohd Shafian (Universiti Sains Malaysia, 2006)
This project is to design a traffic light with sensor using FPGA (Field Programmable Gate Array). This design of traffic light is using sensor for the entire road in the junction. The sensor will sense the vehicle in that junction and will control the system depending on the vehicle that will be sense by the sensor. This project can be use for 24 hour and can be classified with other condition. The idea for this project was started from the beginning and the idea will presented to block diagram. From the block diagram this project will be designing using Xilinx. The design of this project will transfer to IC EPROM and the objective for this project will be seen on the board Xilinx. This system can function very effective and can be used for many other conditions.